EVALUATION OF ADDITIONAL FOOD PROGRAM FOR SCHOOL CHILDREN - Muhammad Bintang DARMAWAN; Ihsana El KHULUQO (Journal of Education and Leadership in Education, 2020)
This research aims to see the level of success in achieving the goals set for the Evaluation of School Child Supplement Program. This research is a qualitative descriptive study using an evaluation Discrepancy Evaluation Model (DEM) Input, Process, Output, to find out the level of success in achieving the goals set at Evaluation of Service Quality in School Child Supplement Program at SDN Pluit 03 Kelurahan Pluit North Jakarta. The subjects of this study were the Principal, Vice Principal and Chair of the Committee. Data collection techniques with the study of documentation, observation and interviews. Data analysis uses an interactive analysis model that is data collection, data reduction, data presentation and drawing conclusions. Input Components, all predetermined criteria for program implementation program Provision of Supplementary Food for School Children the input component is already good but there are components which have not been met related to additions to support the activities of School Child Supplementary Food Program to a better way. Process Components, there are some standards that are not implemented such as not carrying out deliberation activities, teachers have not fully carried out the mentoring properly, there are still teachers who do not accompany students, provide direction, or monitor. Output Components, standards that have been set based on output components are already good but not optimal occurs in community participation as supervisors not going well.